Policy responses from countries with the highest number of COVID-19 deaths in the world: a scoping review (Research, Society and Development, 2022)
The COVID-19 pandemic has been declared since March 11, 2020. Until December 2020, the absence of specific treatments or vaccines for COVID-19 implied the need to use non-pharmacological strategies to reduce infection rates. This study aimed to track and compare the policy responses of countries with the highest number of COVID-19 deaths in the world. Was performed a scoping search in five databases (PubMed, Scopus, LILACS, Web of Science and Google Scholar) between December 1, 2019 and April 30, 2020. Information on policy and health on official websites of the listed countries was also searched. After the selection process, which was carried out independently by two evaluators following the previously established criteria, 55 titles were included. Of the 18 documents of national health societies, 13 addressed the prevention of COVID-19. The most reported country was Italy (17). The strategies most cited by the studies are: traveler monitoring, international travel controls, social distancing orders, closure schools and universities, partial and total lockdown. Until the end of April, all countries evaluated, United States, Italy, the United Kingdom, Spain, France, Belgium, Germany, Iran, Brazil and the Netherlands, have adopted measures such as social distancing orders and the closure of schools and universities. Except for Iran, all these countries have adopted some type of lockdown. So far (August, 2022), Germany has already been cited as an example of a successful country in controlling the pandemic, while the United States still has the highest numbers in the world in total cases, total deaths and new deaths weekly from COVID-19.